Functionally Competent, PD-1+ CD8+ Trm Cells Populate the Brain Following Local Antigen Encounter - Schøller, Amalie Skak; Nazerai, Loulieta; Christensen, Jan Pravsgaard; Thomsen, Allan Randrup (Frontiers in Immunology, 2021)
Expression of programmed cell death-1 receptor (PD-1) has traditionally been linked to T-cell exhaustion, as signaling via PD-1 dampens the functionality of T-cells upon repetitive antigen exposures during chronic infections. However, resent findings pointing to the involvement of PD-1 both in T-cell survival and in restraining immunopathology, challenge the concept of PD-1 solely as marker for T-cell exhaustion. Tissue resident memory T cells (Trms) hold unique effector qualities, but within a delicate organ like the CNS, these protective abilities could potentially be harmful. In contrast to their counterparts in many other tissues, brain derived CD8+ Trms have been found to uniformly and chronically express PD-1. In this study we utilized a recently established model system for generating CNS Trms in order to improve our understanding regarding the role of PD-1 expression by Trms inside the CNS. By intracerebral (i.c.) inoculation with a non-replicating adeno-viral vector, we induced a PD-1hi CD8+ T cell memory population within the CNS. We found that PD-1 expression lowered the severity of clinical disease associated with the i.c. inoculation. Furthermore, high levels of PD-L1 expression was found on the infiltrating monocytes and macrophages as well as on the resident microglia, oligodendrocytes and astrocytes during the acute phase of the response. Additionally, we showed that the intensity of PD-1 expression correlates with local antigen encounter and found that PD-1 expression was associated with decreased CD8+ T cell memory formation in the CNS despite an increased number of infiltrating CD8+ T cells. Most importantly, our experiments revealed that despite expression of PD-1 and several additional markers linked to T-cell exhaustion, Tim-3, Lag-3 and CD39, the cells did not show signs of limited effector capacity. Collectively, these results endorse the increasing amount of evidence pointing to an immune-modifying role for PD-1 expression within the CNS, a mechanism we found to correlate with local antigen exposure.